Вплив інформаційних технологій на якість сучасної фармацевтичної освіти - Стрілкова, Т. О.; Фролова, Н. О.; Стороженко, І.П.; Ромоданова, Е. О. (Sp. z o.o. «Diamond trading tour», 2017)
The report focuses on the study of students’ attitudes to the role of information technology in the educational activity. In this context, analyzed results of the survey conducted among students of different specialties and courses are different perceptions of teachers and students of educational informatization process, studied the materials on the chosen theme
Keywords: інформаційні технології; якість освіти